2011
DOI: 10.1007/s12011-011-9043-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hypoglycemic Activity of Fermented Mushroom of Inonotus obliquus Rich in Vanadium and Wild-Growing I. obliquus

Abstract: The effects of vanadium-enriched and wild Inonotus obliquus were tested on hyperglycemic mice. The vanadium content of the culture medium was 0.6%, reaching a concentration of 3.0 mg/g in the cultured mushroom while in the wild variety is 1/100 of that amount. The toxicity of vanadium at the 3.0 mg/g level is negligible, but its anti-diabetic effects are significantly different to those of the wild variety (p < 0.05). Due to its high bioavailability and low toxicity, vanadium-enriched I. obliquus could be used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…At a dose of 100 mg/kg, a 35.9% increment in tumor metastasis was observed, whereas at a dose of 10 mg/kg, there was 33.4% inhibition of tumor metastasis (Song et al, ). Additionally, a promising antidiabetic therapeutic effect has also been found with vanadium‐enriched I. obliquus (Zhang et al, ), which opens the door to the potential use of this mushroom in combination with metals and other bioactive compounds. It was further reported that the I. obliquus cultured in Tween 80 (nonionic surfactant)‐containing medium improved the production of exopolysaccharides and endopolysaccharides and increased the scavenging activity against DPPH radicals (Xu, Quan, & Shen, ).…”
Section: Limitations and Future Recommendationmentioning
confidence: 99%
“…At a dose of 100 mg/kg, a 35.9% increment in tumor metastasis was observed, whereas at a dose of 10 mg/kg, there was 33.4% inhibition of tumor metastasis (Song et al, ). Additionally, a promising antidiabetic therapeutic effect has also been found with vanadium‐enriched I. obliquus (Zhang et al, ), which opens the door to the potential use of this mushroom in combination with metals and other bioactive compounds. It was further reported that the I. obliquus cultured in Tween 80 (nonionic surfactant)‐containing medium improved the production of exopolysaccharides and endopolysaccharides and increased the scavenging activity against DPPH radicals (Xu, Quan, & Shen, ).…”
Section: Limitations and Future Recommendationmentioning
confidence: 99%
“…Among all the active components in Inonotus obliquus , Inonotus obliquus polysaccharides have the broadest biological activity, such as anticancer, hypoglycemic, anti-inflammatory, and anti-oxidation effects [ 8 , 22 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Through the number of Scopus-indexed publication numbers (archived until 15 March 2021) for polysaccharide bioactivity, Inonotus obliquus , Inonotus obliquus polysaccharide related articles, a certain degree of upward trend can be seen ( Figure 1 ), which means that the medicinal value and health value of Inonotus obliquus have been widely recognized and affirmed [ 5 , 6 , 62 , 63 , 64 ], making it worthwhile to review Inonotus obliquus polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the limitations and unmet goals associated with anti-diabetic drugs, an increased number of diabetic patients globally currently resort to complementary and alternative medicine [ 5 ]. Therefore, natural and non-toxic anti-diabetic drugs are inevitable for diabetic therapeutics such as exopolysaccharides (EPSs) [ 6 ]. Metabolic abnormalities and oxidizing stress arise at early stages of diabetes and are significant risk factors for complications of the nervous, cardiovascular, excretory, and reproductive systems [ 7 ].…”
Section: Introductionmentioning
confidence: 99%